The Conceptual Framework of Spiritual Health in Islamic Resources (the Quran and Nahjul-Balagha( - Mostafa Esmaeili; Mahdi Fani; Marzieh Karamkhani (پژوهش در دین و سلامت, 2017)
For downloading the full-text of this article please click here.